Thrust Bearing with Rough Surfaces Lubricated by an Ellis Fluid - Walicka A. (International Journal of Applied Mechanics and Engineering, 2014)
In the paper the influence of bearing surfaces roughness on the pressure distribution and load-carrying capacity of a thrust bearing is discussed. The equations of motion of an Ellis pseudo-plastic fluid are used to derive the Reynolds equation. After general considerations on the flow in a bearing clearance and using the Christensen theory of hydrodynamic rough lubrication the modified Reynolds equation is obtained. The analytical solutions of this equation for the cases of a squeeze film bearing and an externally pressurized bearing are presented. As a result one obtains the formulae expressing pressure distribution and load-carrying capacity. A thrust radial bearing is considered as a numerical example.